Standardizing Reinforcement Detailing Practices in Indonesia through SNI 6816:2025 - Sumeru, Indrawati; Sutjipto, Suradjin (Syntax Literate, 2025)
This paper presents SNI 6816:2025, a national standard developed to address the growing need for clarity, consistency, and technical reliability in the reinforcement detailing of reinforced concrete structures in Indonesia. For more than two decades, SNI 6816:2002 had served as the primary reference, but it no longer reflected advancements in structural design codes, particularly SNI 2847. In response, SNI 6816:2025 was formulated by adopting and adapting technical content from ACI MNL-66(20), while aligning with Indonesian practices and regulations, including reinforcement notations and material specifications from SNI 2052. The standard is structured in two main parts. The first part is a direct adoption of ACI 315R-18, covering the principles of presenting reinforcement details. The second part contains 109 reinforcement details for key structural elements—slabs, beams, columns, walls, foundations, and slabs-on-ground—supported by clear illustrations and notes referencing the relevant clauses in SNI 2847. Additional appendices provide practical design tables and source references. All imperial units have been converted to SI units through hard conversion, and all numerical values recalculated to meet national requirements.SNI 6816:2025 is intended not only as a technical reference but as a standardization tool to support more accurate, coordinated, and verifiable reinforcement detailing practices. Its implementation is expected to enhance communication among engineers, detailers, and contractors, reduce errors in construction drawings, and promote higher-quality outcomes in structural concrete projects throughout Indonesia.